Analisis Kelayakan Usaha Udang Vannamei Di Desa Bumi Pratama Mandira Kecamatan Ogan Komering Ilir Kabupaten Sumatera Selatan - Riswanto Sinaga; Aminah Aminah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
To determine whether or not a business is feasible, a business feasibility analysis is needed. This study will analyze the feasibility of vannamei shrimp pond cultivation in Bumi Pratama Mandira Village, Ogan Komering Ilir Regency, South Sumatra Province which is carried out semi-intensively so that it can lead to the possibility of experiencing profits or losses. The purpose of the study was to determine the amount of investment costs, total production costs, income and income as well as a feasibility study using the calculation of Break Even Point (BEP), R/C Ratio, B/C Ratio, Return on Investment (ROI), and Payback Period. (PP) vannamei shrimp farming business. This research is a qualitative and quantitative research. The population in this study were people who worked as vaname shrimp cultivators in Bumi Pratama Mandira Village, so that in this study a sample of 3 vaname shrimp cultivators was used using purposive sampling technique as a sampling technique. Types of research data in the form of primary data and secondary data. The results of this study are the third effort of vannamei shrimp farmers in Bumi Pratama Mandira Village, Ogan Komering Ilir District, South Sumatra Regency.